Effect of sprouted papaya seed meal on physiological conditions, intestinal bacterial populations and meat quality of broilers - Sugiharto, S.; Winarti, W.; Widiastuti, E.; Yudiarti, T.; Sartono, T. A.; Wahyuni, H. I.; Pratama, A. R. (Diponegoro University, 2022)
The study investigated the effect of sprouted papaya seed meal (SPSM) on physiological conditions, intestinal bacteria and meat quality of broilers. A 390 broiler chicks were distributed to T0 (control feed), T1 (feed with 2.5% papaya seed meal [PSM]), T2 (1% SPSM), T3 (2.5% SPSM), and T4 (5% SPSM). Blood, intestinal digesta and meat were obtained at day 36. Feeding 2.5% PSM lowered (P<0.05), but SPSM up to 5% had no effect on daily gain. PSM reduced (p<0.05) feed intake, but not SPSM. Feed efficiency was lower (P<0.05) in T4. Feeding 5% SPSM increased (P=0.06) bursa of fabricius. T1, T3 and T4 had lower (P=0.09) heterophils. Mean corpuscular haemoglobin and mean corpuscular haemoglobin concentration were lower (P<0.05) in T4. Cholesterol to high-density lipoprotein (HDL) ratio of PSM and SPSM was lower (P<0.05) than control. SPSM at 2.5% increased (P<0.05) serum HDL. PSM-fed birds had lower cholesterol (P=0.07), triglyceride (P=0.09) and lowdensity lipoprotein (P=0.09). PSM or SPSM decreased (P<0.05) serum total protein, albumin and globulin. PSM and SPSM reduced (P<0.05) creatinine. Alanine aminotransferase was reduced (P<0.05) with SPSM at 1 and 2.5%. Ileal lactic acid bacteria to coliform ratio in PSM and SPSM was greater (P<0.05) than in control. Ileal coliform was lower (P=0.08) in PSM and SPSM. PSM reduced (P=0.08) saturated fatty acids, while 1 and 2.5% SPSM increased (P=0.09) unsaturated fatty acids contents of meats. In conclusion, SPSM improved immune competence, blood lipid profile and gut bacterial population of broilers.